Sweeping of the fetal membranes and its effect on duration of pregnancy in low risk cases - Batham, Sonu Kumar; Kori, Archana; Sirpurkar, Manik S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: This study aimed to determine effectiveness of sweeping of membranes on the duration of pregnancy at term, and its effect on maternal and neonatal outcomes. Methods: In this prospective study, 145 women with uncomplicated pregnancy at 39 weeks or more gestation who were attending regular ANC clinic, were recruited for study, out of them 60 were cases (sweeping group) and 85 were control (no sweeping group). Primary outcome measure was occurrence of spontaneous labour and total duration of pregnancy. Other outcome measures included were interval of onset of labour from membrane sweeping, incidence of premature rupture of membranes, total duration of active labour, mode of delivery, rate of caesarean section and causes, and neonatal and maternal outcome. Results: There were no statistically significant differences between the two groups regarding maternal age, parity and bishops score at recruitment. There was a significant difference observed in spontaneous labour rate and interval time between recruitment to delivery in groups. There was no significant difference regarding mode of delivery, maternal and fetal outcomes. Conclusions: Membrane sweeping is a safe procedure that reduces the incidence of post-term pregnancies if applied at term.